Experiencing Change: A Phenomenological Exploration (Existential Analysis: Journal of the Society for Existential Analysis, 2015)
This paper explores the experience of change from a phenomenologically-attuned perspective. It proposes three variants of change experience, of which the third, those change experiences that are reflectively troubling and deemed to be destructive, undesirable, and debilitating, is particularly pertinent to therapeutic practice. Further, the paper explores various paradoxes and polarities associated with the experience of change and considers what factors may be involved that shift our relationship to change from that of being unwanted and dangerous towards that of a reflective willingness 'to meet' change experiences and engage with their existential possibilities.
Keywords: Spontaneously accepted change; reflectively accepted change; reflectively troubling or rejected change; change polarity of disruption/continuity; death anxiety